Analysis of Neutronic Safety Parameters of the Multi-Purpose ReactorGerrit Augustinus Siwabessy (RSG-GAS) Research Reactor at Serpong - Tukiran Surbakti; Purwadi Purwadi (Universitas Negeri Surabaya, 2019)
The main safety parameters of Multipurpose ReactorGerrit Augustinus Siwabessy (RSG-GAS) have never been evaluated periodically and neutronically require to be evaluated in terms of stuck rod reactivity, shut-down margin and temperature reactivity coefficient are treated by experiment. Meanwhile, power peaking factors and maximum fuel burn up are treated by calculations. The diffusion method did the calculation using the computer code. Safety parameters are very important aspects for the operation and design improvement. The results of the experiment and calculation about the safety parameters of RGS-GAS core are utilized for safety evaluation as part of a research reactor operation Periodic Safety Review (PSR). It presents reactor calculations as a method for their determination assuming use of computer codes such as WIMSD-5B using ENDF.BVII.0 and BATAN-FUEL. According to the experimental data and calculation, neutronic safety parameters have met the safety analysis report such as reactivity coefficient is negative and met the shutdown margin at stuck rod condition nothing has violated the safety margin. The results can be used as the periodic safety review for renewal operation license from Nuclear Energy Regulatory Agency of Indonesia (BAPETEN) as the regulator body. These results also can be used as a reference for new research reactor MTR type advanced design in the future.